A família na rotina pedagógica do atendimento educacional especializado: uma proposta de intervenção na Sala de Recursos Multifuncionais - PEREIRA, Cleomar Lima (2020)
This research had like general objective build collectively a pedagogical notebook with methodological strategies for the participation of parents and guardians in the routine of specialized educational assistance in the multifunctional resource room. Quantitative and qualitative approach research from an exploratory/descriptive study, it is a proposal for pedagogical intervention from the perspective of participant research and with a collaborative focus. The participants involved were 1 (one) teacher in the multifunctional resource room, 1 (one) pedagogical coordinator and 10 (ten) parents and guardians and 10 (ten) students with disabilities and autism spectrum disorder enrolled in the municipal school of specialized educational assistance Dra. Maria Amélia Bastos, located in the city of São José de Ribamar/MA. The instruments of generation and data collection used consisted of a questionnaire, interviews and participant observation. The presentation and discussion of results were carried out under the technique of discourse analysis and content categorization. For the results involving the perception of parents and guardians about the interventions carried out, we found that 40% and 30% of them know „little‟ or „something‟ about their children's growth or learning, respectively and 90% say know 'little' or 'nothing' about their rights in relation to the children's needs and that is why we identified that 50% of the participants reported that in „nothing‟ they can help their children and 80% „nothing‟ manage to perform their own needs, however, although some limitations, 60% say the intervention is „very useful‟. The interview conducted with the teacher demonstrated the need to reframing the concept of parents/ guardian participation, understood as passive action, dynamic, inserted in the construction and decision processes inserted. The achievement of the pedagogical intervention had good acceptance and satisfaction on the part of those involved who reported positive impacts in relation to the collaboration and the acquired learned. The intervention under a collaborative perspective evidenced the need for a training and orientation project for parents and guardians that helps them to participate in educational interventions developed with students.